The The Implementation on Genre Approach on Students' Skill in Writing Anecdote Text at Senior High School: The Implementation on Genre Approach on Students' Skill in Writing Anecdote Text at Senior High School - Affan Lubis; Azhary Tambusai; Ahmad Laut Hasibuan (International Journal of Educational Research Excellence (IJERE), 2022)
This study aims is to determine the results of the development of interactive multimedia-based anecdotal text learning modules by students State of Vocational High School 1 of Batang Toru. The module developed is in the form of a digital module. This type of research is development research based on the 4-D development model. With the subject of the trial consisting of design experts, material experts, Indonesian language teachers, and class X students of State of Vocational High School 1 Batang Toru. The results showed that (1) the validation of the material experts included the content eligibility is 88.0% in the good category, the feasibility of presenting is 93.7% learning module Very good category, Interactive Mutimedia aspects is 95.8% very good category, language assessment aspects 92, 5% category is very good, and aspects of project based learning is 83.3% Good category (2) validation of design experts includes initial design is 89.2% with good category, content design is 83.9% good category, digital module typography is 83.3 category good, and 87.5% illustration in good category. (3) limited trials obtained a score is 82.79% with good criteria. (4)Expanded trials obtained a score is 80.04% in the good category. The difference obtained was 13 from before and after using a digital module. This research has implications, namely the module developed will contribute to the practice, especially in the implementation of the learning process for teachers as additional teaching materials to provide convenience to the material being taught can be independent or classical. Keywords : Digital Modules; Anecdotal Texts.